Racial inequality in COVID-treatment and in-hospital length of stay in the US over time - Althouse, Benjamin M.; Baker, Charlotte; Smits, Peter D.; Gratzl, Samuel; Lee, Ryan H.; Goodwin Cartwright, Brianna M.; Simonov, Michael; Wang, Michael D.; Stucky, Nicholas L. (Frontiers in Public Health, 2023)
Introduction Demonstrated health inequalities persist in the United States. SARS-CoV-2 (COVID) has been no exception, with access to treatment and hospitalization differing across race or ethnic groups. Here, we aim to assess differences in treatment with remdesivir and hospital length of stay across the four waves of the pandemic. Materials and methods Using a subset of the Truveta data, we examine the odds ratio (OR) of in-hospital remdesivir treatment and risk ratio (RR) of in-hospital length of stay between Black or African American (Black) to White patients. We adjusted for confounding factors, such as age, sex, and comorbidity status. Results There were statistically significant lower rates of remdesivir treatment and longer in-hospital length of stay comparing Black patients to White patients early in the pandemic (OR for treatment: 0.88, 95% confidence interval [CI]: 0.80, 0.96; RR for length of stay: 1.17, CI: 1.06, 1.21). Rates became close to parity between groups as the pandemic progressed. Conclusion While inpatient remdesivir treatment rates increased and length of stay decreased over the beginning course of the pandemic, there are still inequalities in patient care.